The F.R.E.I.H.E.I.T. Project: tackling disinformation in Eastern Europe - Euractiv (Euractiv, 2025)
The F.R.E.I.H.E.I.T Project is a bold and ambitious initiative currently tackling the growing threat of disinformation, particularly in Europe’s Eastern Neighbourhood. It is expanding its focus to critical areas such as energy, agriculture, security, and migration, all of which are vulnerable to manipulation.
Europe